DISCURSIVE PROOF OF THE CONTEST FOR SOCIO-EDUCATIONAL TECHNICAN: PUBLIC SERVER’S RESPONSIBILITY TO THE SOCIETY - Silva, Roniclésia Soares da; Firmino, Alessandra Cristiane da Silva (Revista Coleta Científica, 2019)
This is a review of the article entitled “Discursive Proof of the Contest for Socio-Educational Technician: Responsibility of Public Servants Before Society”. This article is authored by: Jonas Rodrigo Gonçalves; Thiago Monteiro Cruz. The article reviewed here was published in the jornal “Revista JRG de Estudos Acadêmicos”, in Year I, n. 1.